The Naples warped hard chine hulls systematic series. (15th July 2017) - De Luca, F.; Pensa, C.
Abstract: An experimental study was carried out to evaluate still water performance of a Systematic Series of hard chine hulls in planing and semiplaning speed range. Models of the Naples Systematic Series ( NSS ) were of varying length-to-beam ratios of the parent hull. The parent hull, shaped with warped bottoms, was derived from a pre-existing hull extensively tested in a towing tank. This hull was validated by many work boats built in the last fifteen years. To simplify the construction of vessels with rigid panels (aluminium alloy, plywood or steel) the original hull form was transformed to obtain developable hull surfaces. The models were tested at Re>3.5×10 6, in speed ranges Fr=0.5−1.6 and Fr∇ =1.1−4.3. The series studies the influence of LP /BC and Ⓜ ratios that vary respectively in the ranges of 3.45–6.25 and 4.83–7.49, for two positions of CG. All the models were tested both with and without interceptors. To enable model-ship correlation following the ITTC recommendations, in addition to the resistance coefficients of the models, dynamic wetted lengths and surfaces were provided as tables. To facilitate the implementation of Velocity Predict Programs, all the data (resistances, lengths and surfaces) were also furnished in polynomial form. In addition to the use of series in the design field, this study was done to provide data to improve the numerical simulations of a planing craft. With this aim, in addition to the resistance data, the wave profiles, obtained by wave cuts, were provided to carry out validation procedures. Highlights: Performance in still water of a Systematic Series of five models are furnished. The performance are estimated by towing tank tests. The models have been tested with and without interceptors. To be used as benchmark, results have been enriched with wave patterns data.